2019
DOI: 10.1002/adsc.201900776
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox Alkylarylation of N‐Benzyl‐N‐(2‐ethynylaryl)‐Amides with α‐Bromoalkyl Esters: Access to Dibenzazepines

Abstract: A new two‐component alkylarylation of N‐benzyl‐N‐(2‐ethynylaryl)amides with α‐bromoalkyl esters using visible light photoredox catalysis promoted by silver salts for producing substituted dibenzazepines is described. Employing α‐bromoalkyl esters to form the alkyl carbon‐centered radicals enables the alkylarylation of alkynes where two carbon‐centered functional groups are introduced across the C≡C bond in a single reaction.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The electrocatalytically generated CHF 2 radical reacts with alkyne 71 to generate dibenzazepine 72 [85] . Similar radical cascades has been employed by others to generate functionalized dibenzazepines [98–100] …”
Section: Molecular Electrocatalysismentioning
confidence: 79%
“…The electrocatalytically generated CHF 2 radical reacts with alkyne 71 to generate dibenzazepine 72 [85] . Similar radical cascades has been employed by others to generate functionalized dibenzazepines [98–100] …”
Section: Molecular Electrocatalysismentioning
confidence: 79%
“…In the same year, Hu, Li, and co-workers used α-bromoalkyl ester as the radical precursor, fac -Ir(ppy) 3 as PC, and the silver salt (AgOAc) acted as a scavenger for the bromide ion to facilitate the reaction (Scheme 27). 53 To our delight, in contrast to a previous study, acetyl groups linked to nitrogen atoms have also been shown to be feasible.…”
Section: Visible Light-induced Systemmentioning
confidence: 68%
“…On the basis of the above observations and previous reports, , the plausible mechanism of this reaction is then proposed (Scheme ). Initially, CF 3 radical is generated via a single electron transfer (SET) process from Cu­(I) species to Togni-II reagent, accompanied by the formation of the anion species D and Cu­(II) species.…”
mentioning
confidence: 76%
“…Particularly, as an excellent radical acceptor, alkynes could be utilized for facile construction of complex functional molecules because of the high activity of the in situ formed vinyl radical, which could induce further cascade reactions. , We assumed that a rapid and efficient access to 7-membered cyclic sulfonamides might be gained by direct intramolecular radical addition to the aromatic ring of a vinyl radical intermediate. Considering that only limited examples were reported for the synthesis of dibenzazepines via an electrochemical or photocatalytic protocol using this strategy, this tactic needs further development to complement the current methodologies in organic synthesis. As part of our interest in the construction of 7-membered rings, as well as the fact that the incorporation of CF 3 into organic molecules could obviously enhance the lipophilicity, metabolic stability, and bioavailability, we report a novel and facile approach to synthesize dioxodibenzothiazepines via copper-catalyzed trifluoromethylation/cyclization of terminal alkynes by radical relay.…”
mentioning
confidence: 99%